Statins and Elderly: From Clinical Trials to Daily Practice - Verdoia, Monica; Galasso, Gennaro; Filardi, Pasquale P.; De Luca, Giuseppe (Current Vascular Pharmacology, 2019)
Elderly patients represent a rising social problem, due to the exponential growth of persons in these age groups and their atherothrombotic burden. The management of this population still raises several challenges, requiring a balance between elevated cardiovascular risk, clinical complexity, frailty and co-morbidities. Statins represent the main pillar in cardiovascular prevention, lowering serum cholesterol and reducing mortality and ischemic events, especially in high-risk patients. Yet, elderly patients have often been excluded from major clinical trials of statins, thus limiting the experience with these drugs in advanced age. Moreover, important barriers to the use of statins in the elderly exist due to potential risks attributed to altered metabolism, comorbidities, polypharmacy and drug-drug interactions and financial constraints. This situation has led to a “statin paradox”, since high-risk elderly patients, that would most benefit from the use of statins, may be undertreated with these drugs in real life. The vague indications provided by guidelines mean that this issue is still debated, especially regarding primary prevention. Nevertheless, the benefits in outcome offered by statins cannot be neglected. Efforts should be made in order to focus on the importance of statin use in the elderly and to provide clinicians with adequate tools for case by case decisions.
Keywords: polypharmacy